Structural analysis of the SRP Alu domain from Plasmodium falciparum reveals a non-canonical open conformation - Soni, Komal; Kempf, Georg; Manalastas-Cantos, Karen; Hendricks, Astrid; Flemming, Dirk; Guizetti, Julien; Simon, Bernd; Frischknecht, Friedrich; Svergun, Dmitri I.; Wild, Klemens; Sinning, Irmgard (Communications biology, 2021)
The eukaryotic signal recognition particle (SRP) contains an Alu domain, which docks into the factor binding site of translating ribosomes and confers translation retardation. The canonical Alu domain consists of the SRP9/14 protein heterodimer and a tRNA-like folded Alu RNA that adopts a strictly ‘closed’ conformation involving a loop-loop pseudoknot. Here, we study the structure of the Alu domain from Plasmodium falciparum (PfAlu), a divergent apicomplexan protozoan that causes human malaria. Using NMR, SAXS and cryo-EM analyses, we show that, in contrast to its prokaryotic and eukaryotic counterparts, the PfAlu domain adopts an ‘open’ Y-shaped conformation. We show that cytoplasmic P. falciparum ribosomes are non-discriminative and recognize both the open PfAlu and closed human Alu domains with nanomolar affinity. In contrast, human ribosomes do not provide high affinity binding sites for either of the Alu domains. Our analyses extend the structural database of Alu domains to the protozoan species and reveal species-specific differences in the recognition of SRP Alu domains by ribosomes.
Gesehen am 29.07.2021